The effectiveness of low power laser and occlusal plate in the treatment of temporomandibular dysfunctions: a literature review (Research, Society and Development, 2022)
Temporomandibular dysfunctions (TMD's) represents a set of functional and structural disorders of the stomatognathic system. The main causes of non-dental pain in the orofacial region are considered. Its treatment modalities are diverse and depend essentially on diagnosis. This work aims to clarify the efficacy of low-power laser associated or not with occlusal plaque in the treatment of temporomandibular dysfunctions. Studies published from 2016 to 2022 were selected through the databases: National Library of Medicine (PubMed), Scientific Electronic Library (SciELO) and ScienceDirect. The descriptors employed were: Dysfunction/Tempromandibular Disorders; Occlusal Splint; Low-Power/Low-Level Laser and Boolean and operator between them. We included studies that related low-power laser and occlusal plate individually and jointly as a therapeutic approach for the treatment of temporomandibular dysfunctions, with 16 of which were selected. The literature indicates therapeutic effectiveness for both associates and/or isolates for the treatment of TMDs, but there are controversies about the indication of the two noninvasive therapeutic methods. There is a scarcity of clinical studies that proves the efficacy of these treatments and, also, great heterogeneity of the protocols addressed, making it difficult to parameterize the effectiveness of therapies.